REFRAMING EDUCATION: INDIGENOUS VALUES-BASED PEDAGOGY FOR HOLISTIC DEVELOPMENT - Akmal Mundiri (Nurul Jadid University, Paiton Probolinggo, East Java, 2024)
This study aims to analyze the integration of local wisdom values into learning design and practices and examine their contribution to the holistic development of students. The study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that indigenous values were systematically integrated into the learning process through planning, pedagogical interactions, and contextual learning activities. This integration has been shown to encourage character development, such as responsibility, respect, and ethical decision-making. In addition, learning based on local cultural practices provides authentic learning experiences through direct involvement in community activities and self-reflection, thus contributing to students' cognitive, emotional, social, and spiritual development. These findings confirm that learning based on local wisdom not only strengthens cultural identity but also creates a more meaningful and relevant learning process to real life. Thus, this study contributes to the development of a contextual, humanistic, and sustainable education model. The implications of the study indicate the importance of teachers' roles in integrating local values and creating reflective learning experiences, as well as the need for institutional support in building collaborations with cultural communities. This approach has the potential to be a strategic alternative in addressing educational challenges in the global era.